(untitled) (UNED Research Journal, 2019)
Climate change threatens artisanal fisheries and small-scale marine and coastal tourism as well as the folks who depend on these activities, particularly in developing regions. Urgency lies in adopting measures to ensure these livelihoods and conserve the natural resources on which they depend. MarViva Foundation selected community-based fishing and tourism associations from the Gulf of Montijo on Panama´s Pacific coast for climate change adaptation measure implementation support based on their degrees of climate change risk. MarViva estimated degrees of risk of the fishing and tourism sectors by modeling three components that upon interacting generate climate change risk – vulnerability, hazard and exposure. The main result, a community-scale climate change risk index, provided an objective criterion for selecting beneficiary groups and laid the groundwork for designing specific interventions aimed at building resilience and reducing climate change risk drivers relevant to the artisanal fishing and small-scale tourism sectors in the Gulf of Montijo.